Pengentasan Kemiskinan Melalui Program Bantuan Tunai Bersyarat di Desa Lagundi Kecamatan Kambowa Kabupaten Buton Utara - Ashmarita Ashmarita; Abdul Jalil; Laras Laras; Abdul Alim (Empower : Jurnal Pengembangan Masyarakat Islam, 2023)
This study investigates the Family Hope Program in Lagundi Village, Kambowa District, North Buton Regency. The primary aim of this research is to assess and elucidate the effects and effectiveness of the Family Hope Program in eradicating poverty in Lagundi Village. Furthermore, it seeks to highlight that whether it's conditional or unconditional, direct cash assistance essentially serves the same purpose, which is centered on poverty alleviation. This paper not only discusses the Family Hope Program's role in poverty reduction but also delves into the concept of conditional cash transfers (CCT), which stands in contrast to Unconditional Cash Transfers (UCT) or unconditional financial aid. In addition, CCT acts as an entry point for poverty eradication. Every individual registered as a beneficiary must meet specific criteria: PKH is primarily aimed at fulfilling basic needs, such as providing nutrition to enhance physical strength and health through adequate nutrient intake. Besides, it involves meeting health quality criteria by offering facilities like BPJS. The final requirement for PKH is the engagement of village residents in twelve years of compulsory education. The research methodology comprises direct field observations and interviews. The collected data are then analyzed using a qualitative descriptive approach. Research findings suggest that the Family Hope Program in Lagundi Village has yielded positive outcomes, including the fulfillment of basic needs, improved health quality, and increased access to education for children. Nevertheless, the program also exhibits negative aspects related to deficiencies in program management.